2005
DOI: 10.1002/hep.20664
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia and the MTHFR C677T polymorphism promote steatosis and fibrosis in chronic hepatitis C patients†‡

Abstract: The factors and mechanisms implicated in the development of hepatitis C virus (HCV)-related steatosis are unknown. Hyperhomocysteinemia causes steatosis, and the methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism induces hyperhomocysteinemia. We investigated the role of these factors in the development of HCV-related steatosis and in the progression of chronic hepatitis C (CHC). One hundred sixteen CHC patients were evaluated for HAI, fibrosis and steatosis grades, body mass index, HCV genotypes, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
97
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 36 publications
1
97
1
3
Order By: Relevance
“…This is based on the recent report that the MTHFR C677T polymorphism is associated with steatosis and fibrosis in chronic hepatitis C patients. 51 Reduced MTHFR activity can reduce the SAMe pool (especially if folate is deficient), and we have accumulating evidence especially in animal models that chronic hepatic SAMe deficiency can predispose to HCC. 22 Reduced SAMe availability can lead to global DNA hypomethylation, which occurs in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the recent report that the MTHFR C677T polymorphism is associated with steatosis and fibrosis in chronic hepatitis C patients. 51 Reduced MTHFR activity can reduce the SAMe pool (especially if folate is deficient), and we have accumulating evidence especially in animal models that chronic hepatic SAMe deficiency can predispose to HCC. 22 Reduced SAMe availability can lead to global DNA hypomethylation, which occurs in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, MTHFR C667T has also been associated in several reports with an increased risk of invasive cervical cancer and premalignant lesions [21], which also indicate a possible role of MTHFR in viral infection associated cancers. Further, MTHFR C677T polymorphism is associated with hype-rhomocysteinemia among patients with chronic hepatitis C infection [22], which may accelerate the progression of liver fibrosis in CHC and possibly lead to liver cancer. It would be interesting to evaluate the potential interaction between MTHFR and HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the C677T polymorphism of the MTHFR gene was associated with both hyperhomocysteinaemia and a greater degree of steatosis in CHC patients. 16 Our data show that also adiponectin may be implicated in the pathogenesis of CHC-related steatosis. Adiponectin is secreted by adipocytes and has antilipogenic effects that may protect non-adipocyte tissues, such as the liver, from fat accumulation.…”
mentioning
confidence: 56%